Cartilage oligomeric matrix protein as a marker of progressive liver fibrosis in biliary atresia - Wanvisa Udomsinprasert (Nature Portfolio, 2021)
Abstract This study aimed to determine whether mRNA and protein levels of cartilage oligomeric matrix protein (COMP), a glycoprotein responsible for modulating homeostasis of extracellular matrix, in the systemic and local liver environments were associated with clinical parameters of biliary atresia (BA) patients and might serve as a biomarker for BA severity. COMP protein levels in the circulation of 96 BA patients and 56 healthy controls and its mRNA and protein expressions in the liver of 20 BA patients and 5 non-BA patients were evaluated using enzyme-linked immunosorbent assay, real-time polymerase chain reaction, and immunohistochemistry, respectively. In the circulation of BA patients, COMP levels were significantly higher than those in healthy controls. Compared with early-stage BA patients, those with advanced-stage including jaundice, fibrosis, and hepatic dysfunction had significantly increased circulating COMP levels. Raised circulating COMP levels were found to be independently correlated with degree of liver fibrosis. Survival analysis showed that elevated circulating COMP levels were significantly associated with decreased survival of BA patients. Receiver-operating characteristic curve analysis unveiled a diagnostic value of circulating COMP as a non-invasive biomarker of BA (AUC = 0.99), with a sensitivity of 100.0% and a specificity of 98.2%. In the liver, both COMP mRNA and protein expressions of BA patients with fibrosis were significantly greater than those of BA patients without fibrosis and non-BA patients. Collectively, increased circulating COMP might reflect unfavorable outcome of BA patients and have potential as a novel biomarker for the disease severity following Kasai-operation.